2022
DOI: 10.5847/wjem.j.1920-8642.2022.027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different versions of the quick sequential organ failure assessment for predicting in-hospital mortality of sepsis patients: A retrospective observational study

Abstract: BACKGROUND:The quick sequential organ failure assessment (qSOFA) is recommended to identify sepsis and predict sepsis mortality. However, some studies have recently shown its poor performance in sepsis mortality prediction. To enhance its effectiveness, researchers have developed various revised versions of the qSOFA by adding other parameters, such as the lactate-enhanced qSOFA (LqSOFA), the procalcitonin-enhanced qSOFA (PqSOFA), and the modified qSOFA (MqSOFA). This study aimed to compare the performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…In contrast to previous studies, addition of lactate measurement did not improve qSOFA sepsis mortality prediction [ 17 21 ]. Our discrepant results do not discount the utility of lactate measurement as there are several methodological and cohort differences between this study and previous reports.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies, addition of lactate measurement did not improve qSOFA sepsis mortality prediction [ 17 21 ]. Our discrepant results do not discount the utility of lactate measurement as there are several methodological and cohort differences between this study and previous reports.…”
Section: Discussioncontrasting
confidence: 99%
“…Whether qSOFA has prognostic value for patients with sepsis in low resourced ICUs where Acute Physiology and Chronic Health Evaluation (APACHE) II score or SOFA may not be practical has not been robustly assessed [ 10 , 11 ]. Recent evidence from low resource settings does suggest qSOFA is associated with mortality in hospitalized patients with infection [ 12 16 ].The addition of lactate has also been shown to improve qSOFA sepsis mortality prediction in all income settings [ 17 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In predicting in-hospital mortality, the lactate-enhanced qSOFA and modified qSOFA outperformed the qSOFA with the area under the curve (AUC) of 0.740 and 0.731, a sensitivity of 64.36% and 51.40%, and a specificity of 70.78% and 80.96%, respectively. 27 Similarly, Guarino et al used qSOFA, MqSOFA along with lactate assay, and national early warning score (NEWS) to analyze data of sepsis and septic shock patients (n = 556). The author found that MqSOFA, NEWS, and lactate assay scores are more significant predictors of in-hospital mortality than qSOFA, with p < 0.001.…”
Section: Resultsmentioning
confidence: 99%
“…Another subgroup analysis was undertaken by classifying the index test (qSOFA-lactate) into score or criteria groups. In the qSOFA-lactate score group (19,21,27,29,31,35,(37)(38)(39)(40)43), the pooled sensitivity and speci city were 80.1% (95% CI 65.9%, 89.3%; I 2 = 97%, p < 0.01) and 66.1% (95% CI 49.5%, 79.5%; I 2 = 100%, p = 0), with AUC = 0.78 (95% CI 0.73, 0.82), whereas in the qSOFA-lactate criteria group (16,20,21,26,28,32,33,36,41,42), the pooled sensitivity and speci city were 81.6% (95% CI 70.1%, 89.4%; I 2 = 98%, p < 0.01) and 59.1% (95% CI 44.1%, 72.5%; I 2 = 100%, p = 0), with AUC = 0.76 (95% CI 0.73, 0.79).…”
Section: Discussionmentioning
confidence: 99%